Influence of front surface single-pulse laser drilling on a bifacial solar cell determined through simulation and experiment - Rohaizar M.H.; Sepeai S.; Ker P.J.; Ludin N.A.; Ibrahim M.A.; Sopian K.; Zaidi S.H. (Springer, 2023)
High power lasers; Infill drilling; Light scattering; Solar cells; Topography; Transmissions; Bifacial solar cells; Cell efficiency; Cell topography; Crystallographic defects; Light scattering and absorptions; Optical characterisation; Single pulse drilling; Single-pulse laser; Light transmission